2023
DOI: 10.1111/apha.14016
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of the mitochondrial pyruvate carrier: New insights into its structure, function, and inhibition

Sotiria Tavoulari,
Maximilian Sichrovsky,
Edmund R. S. Kunji

Abstract: The mitochondrial pyruvate carrier (MPC) resides in the mitochondrial inner membrane, where it links cytosolic and mitochondrial metabolism by transporting pyruvate produced in glycolysis into the mitochondrial matrix. Due to its central metabolic role, it has been proposed as a potential drug target for diabetes, non‐alcoholic fatty liver disease, neurodegeneration, and cancers relying on mitochondrial metabolism. Little is known about the structure and mechanism of MPC, as the proteins involved were only ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 106 publications
(352 reference statements)
0
2
0
Order By: Relevance
“…This emphasizes the importance of understanding transporter function and characteristics of endogenous substrates that are translocated. So far, the ADP/ATP exchanger and uncoupling proteins (SLC25 family), are the only functional carriers with a characterized structure 187–191 …”
Section: Interaction Of Drugs With Mitochondrial Carriersmentioning
confidence: 99%
“…This emphasizes the importance of understanding transporter function and characteristics of endogenous substrates that are translocated. So far, the ADP/ATP exchanger and uncoupling proteins (SLC25 family), are the only functional carriers with a characterized structure 187–191 …”
Section: Interaction Of Drugs With Mitochondrial Carriersmentioning
confidence: 99%
“…The mitochondrial pyruvate carrier (MPC), whose molecular identity remained elusive for many years, was identified by two groups in 2012 ( Bricker et al, 2012 ; Herzig et al, 2012 ) and shown to be conserved from yeast to mammals. It is a heterodimeric complex formed of MPC1 and MPC2 (also known as SLC54A1 and SLC54A2, respectively) within the inner mitochondrial membrane (see Tavoulari et al, 2019 ; and the recent review by Tavoulari et al, 2023 ). By regulating the transport of pyruvate into the mitochondria, MPC sits at the interface between glycolysis and glucose oxidation, directly influencing the relative rates of each pathway.…”
Section: Transporters In Cancermentioning
confidence: 99%